(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article considers the economic concept of «environmental costs», various interpretations of his domestic and foreign scientists. The changes of the normative-legal legislation concerning expenses on protection of the environment in the modern conditions are investigated. Conducting an analysis of the costs of protecting the environment. The problems of reflection in the accounting and reporting of environmental costs are investigated. The purpose of the article. The purpose of the article. Investigation of the essence, content and role of environmental costs in economic activity, studying the state of expenses on environmental protection in Ukraine. The method (methodology). In this paper we have used the following methods: the method of comparison,method of analysis, method of synthesis, method of abstraction, theoretical method, method of historical and logical generalization. The dialectical method of investigation has become the methodological basis of the research. Results. The essence of the economic concept «ecological costs» and their reflection on the legislative and normative basis are revealed. The analysis of expenses on environmental protection at the expense of own funds of enterprises, organizations, institutions by types of environmental measures in actual prices has been carried out. The dynamics of capital investments on environmental protection and capital repairs of the main means of environmental protection at the expense of own funds of enterprises, organizations and institutions are researched. The dynamics of current expenses for environmental protection at the expense of own funds of enterprises, organizations, institutions and environmental expenditures by sources of financing in 2017 are considered. The problem of displaying environmental costs in accounting and financial reporting is highlighted. Further research seems appropriate to focus on the location of environmental costs in management accounting.